Improvement of Airfoils Aerodynamic Efficiency by Thermal Camber Phenomenon at Low Reynolds Number - Samiee,Ahmad (2018)
ABSTRACT: In this research, viscous, laminar and steady flow around symmetric and non-symmetric airfoils is simulated at Low Reynolds Number (LRN). Navier-Stokes (N-S) equations are discretized by Finite Volume Method (FVM) and are solved by the SIMPLE algorithm in an open source software, namely OpenFOAM. The main objective of this paper is the introduction of the thermal camber phenomenon. This phenomenon is used to improve the aerodynamic performance. Hence, a symmetric airfoil, like NACA0012, with thermal camber is compared with the airfoils with the physical camber, including NACA2412 and NACA4412, to specify which camber type has more effects on the aerodynamic efficiency. Furthermore, various temperatures are tested in order to find the optimum condition. After validation, results indicated that cooling upper surface and heating lower surface, namely thermal camber, generate lift force and improve aerodynamic performance for symmetric airfoils at a 0° Angle of Attack (AOA). These improvements are more than the airfoils with physical camber. Also, when this method is applied to the NACA2412 and NACA4412 airfoils, lift to drag coefficient ratio will increase more than the condition with only cooling or heating the surfaces.